Associations between orbicularis oris thickness and skeletal and dental variables in mixed dentition - Taís de Souza Barbosa; Maria Beatriz Duarte Gavião; Luciana Silveira Pupo; Paula Midori Castelo; Luciano José Pereira
AIM: To evaluate the association between orbicularis oris thickness and skeletal and dental variables in children with mixed dentition. MATERIAL AND METHOD: A convenience sample of 22 children, aged 7 to 12 years, with skeletal Class I and Class II malocclusion and subdivisions were selected. The upper and lower fascicles of the orbicularis oris thicknesses were measured using ultrasound (US) by one calibrated examiner, at rest and in the contracted state. Cephalometric radiograph measurements of the hard and soft tissues were calculated by one trained examiner. The results were analyzed by the Pearson and Spearman coefficients. RESULT: The upper and lower fascicles of the orbicularis oris in the contracted state showed a negative correlation with the distance between Ricketts' E-line and the labrale superius (E ┴ Ls). There were positive correlations between the lower face height and the distance between the AB plane and the labrale superius (AB-Ls) and between the ANB angle and the distance between E ┴ Ls and Ricketts' E-line and the labrale inferius (E ┴ Li). The lower-incisor distance from the N-Pg plane correlated positively with the distance between AB-Ls and the distance between the E ┴ Ls and E ┴ Li. Overbite and interincisal angle were negatively correlated with the distance between the pogonion and the soft tissue pogonion and the distance between E ┴ Li, respectively. CONCLUSION: Skeletal and dental variables were associated with upper and lower lip position and pogonion thickness, while the upper and lower fascicles of the orbicularis oris thicknesses in the contracted state were associated only with upper lip retrusion.